Evaluasi Lanskap Sejarah dan Budaya Berdasarkan Konsep Taman Islami di Area Masjid Agung Keraton Sumenep - Sujai; Soelistyari, Hesti Triana; Alfian, Rizki (Jurnal Lanskap Indonesia, 2024)
The Islamic garden is a garden inspired by the garden of paradise which is often mentioned in the Qur’an and the Hadith of the Prophet. Jannah et al. (2015) conducted a study on Islamic gardens with the method of approaching the value of the content of the Qur’an and hadith, which examined the elements and characteristics of the park as well as sharia boundaries that must be considered in an Islamic garden. This study aims to continue the research which is applied to the mosque garden landscape through the evaluation stage, so that the final result can be recommended in the form of a design based on the concept of an Islamic garden. The research object chosen is the Landscape of the Jamik Sumenep Mosque. This research was conducted using a qualitative descriptive method and literature study, which consisted of the following stages: 1) Evaluation of the mosque garden landscape based on Islamic concepts, 2) User perception analysis, and 3) Preparation of recommendations for the mosque garden landscape design concept. The process of collecting qualitative descriptive data is done by direct observation in the field, interviews with related parties, distributing questionnaires and documentation. While the literature study was taken from the main literature in Islam, namely the Qur’an and hadith, along with other scientific literature related to the Islamic garden. Based on the results of the evaluation and perceptions of respondents, in general the garden landscape of the Jamik Sumenep Mosque is in accordance with the criteria for garden inspiration based on Islamic concepts, there are no garden elements and characteristics that are contrary to sharia. The resulting design recommendations are in the form of a site plan, adding plant species to the garden, adding a sinage, a fountain element, arranging parking lots, structuring circulation paths and adding trash cans. Respondents’ perception stated that the garden landscape of the Jamik Sumenep mosque played a very important role in supporting the function of the mosque as a center of worship. Keywords: Mosque, Landscape Evaluation, Islamic Garden.